Idiopathic Synkinesis of the Facial Musculature: Oculo-Nasal, Oculo-Zygomatic, and Fronto-Nasal Synkinesis. Issue 1 (January 2017) - Bahk, Sujin; Hwang, SeungHwan; Eo, SuRak
Abstract : Abstract: Facial synkinesis is the simultaneous contraction of the certain facial musculature accompanying a motion of designated muscle in the face. With the exception of rare afflictions that are congenital in origin, most patients develop as a sequel to facial nerve paralysis due to trauma, tumor, and surgical injury. As an idiopathic congenital form, oculo-nasal synkinesis which reveals co-contraction of orbicularis oculi and the compressor narium minor muscles which are innervated by separate branches of the facial nerve have been already reported. In addition to oculo-nasal synkinesis, the authors describe 2 more rare patients with facial synkinesis; oculo-zygomatic and fronto-nasal synkinesis with video documentation, which to the best of our knowledge, have not been reported previously in detail. This will help plastic surgeons prevent being involved in legal issues when they might neglect these rare phenomena in preoperative evaluation during cosmetic surgery. Abstract : Supplemental Digital Content is available in the text